Effect of Gadget Use on the Development of Language and Speech Ability in Children Under Five - Purnama, Hanif Wildan; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2024)
Background: Language development is a hierarchical change that begins with hearing and learning through hearing through the sounds of words. This research aims to analyze the effect of gadget use on language and speaking abilities. Subjects and Method: An observational analytical research design using a cross sectional approach was carried out at Bayu Asih Hospital, Purwakarta and Rama Hadi Hospital, Purwakarta in November 2023. A total of 200 children under five were used using a random sampling technique. The dependent variable is language and speech delays. The independent variables are gadget use, mother's employment, mother's education, family income, and child's education. The instruments used were Early Detection of Communication Ability Disorders (DDGKB) and questionnaires. Data analysis uses path analysis. Results: The results of path analysis explain that there is an influence of gadget use (b=1.85; 95% CI=1.02 to 3.40; p=0.044), gender (b=1.85; 95% CI=1.02 to 3.40; p=0.044) and parental income (b =1.85; 95% CI=1.02 to 3.40; p=0.044), mother's employment (b=0.56; 95% CI=0.31 to 1.02; p=0.058), mother's employment (b=0.56; 95% CI=0.31 to 1.02 ; p=0.058) and mother's education (b=0.91; CI 95%=0.48 to 1.73; p=0.783) and child's education (b=0.74; CI 95%=0.42 to 1.34; p=0.325) on speech delays in children. Conclusion: Gadget use, gender, parental income, maternal employment, maternal education, and child education increase the risk of speech delays in children.